Water pool boiling across low pore density aluminum foams. Issue 19 (12th November 2020) - Righetti, Giulia; Doretti, Luca; Sadafi, Hosein; Hooman, Kamel; Mancin, Simone
Abstract: In this paper, experimental data pertinent to deionized water pool boiling across 10 mm thick aluminum foams are presented. Two foam samples with different pore densities, 5 and 10 pores per inch, yet an identical mean porosity of 0.92 are tested. Compared to a heated flat plate, of the same base size, the foams offer higher heat transfer area albeit at induced bubble escaping resistance. The tradeoff between these two effects is investigated. Through the use of high-speed camera recording, bubble generation, trajectory and growth rate were analyzed and critically discussed as functions of the working conditions and of the foam geometry. Furthermore, the experimental data were compared against a correlation appositely proposed for water pool boiling on metal foams. A good degree of agreement was observed.